Curious Encounters Voyaging, Collecting, and Making Knowledge in the Long Eighteenth Century - Craciun, Adriana; Terrall, Mary (University of Toronto Press, 2019)
Curious Encounters uncovers a rich history of global voyaging, collecting, and scientific exploration in the long eighteenth century. Voyagers from Greenland to the Ottoman empire crossed paths with French, British, Polynesian, and Spanish travelers across the world, trading objects and knowledge for diverse ends. The essays in this collection restore our understanding of the encounters between European and Indigenous people. To do this, the essays consider diverse agents of historical change, both human and inanimate: commodities, curiosities, texts, animals, and specimens moved through their own global circuits of knowledge and power. The dynamic contact zones of these curious encounters include the ice floes of the Arctic, the sociable spaces of the tea table, the hybrid material texts and objects in imperial archives, and the collections belonging to key figures of the Enlightenment.